Cardiovascular risk profiles and the uptake of the NHS Healthcheck programme in male prisoners in six UK prisons: an observational cross-sectional survey - Kamlesh Khunti; Richard Morriss; Christopher Packham; Elizabeth Butcher; Marie Williams; Joanne Miksza (BMJ Open)
Introduction Half of all deaths in custody are due to natural causes, the most common being cardiovascular disease (CVD). National Health Service Healthchecks should be available to all eligible prisoners; it is not clear who receives them. Mental health issues are common in prisoners and may affect how healthcare interventions should be delivered. Current policy is to offer Healthchecks to those serving over 2 years in prison.Objectives, methods, setting and design An observational cross-sectional survey in six male prisons in England between September 2017 and January 2019 in prisoners aged 35–74 to identify who was eligible for a Healthcheck and compare CVD risk data with those that were not, and factors associated with uptake.Outcome measures Characteristics of those accepting a Healthcheck were compared with those declining. Assessments of anxiety and depression were compared with CVD risk factors.Results 1207 prisoners completed a Healthcheck. 21.8% of prisoners were ineligible due to existing comorbidities. 76.4% of those invited took up a Healthcheck, and of those, 12.1% were found to have new significant CVD comorbidity. CVD risk was similar to community levels but this population was 10 years younger. Definite case-level depression or anxiety was present in 20.7% and 18.0%, respectively, of participants. An association was found between ethnicity and those invited (p=0.023, φ=0.1) and accepting (p=0.008, φ=0.1) a Healthcheck. 9.7% of prisoners serving less than 2 years had CVD risk scores of 10% or more, and had similar CVD risk profiles but much higher levels of anxiety (p<0.001, φ=0.2) or depression (p=0.009, φ=0.2) than those serving 2 years or more.Conclusion Cardiovascular risk was comparable with community rates and in some prisons, much higher. Rates of anxiety and depression were high. The national policy for selecting prisoners for Healthchecks may leave many high-risk prisoners without appropriate cardiovascular preventative assessments.